APPLICATION OF THE ANALYTIC HIERARCHY PROCESS METHOD FOR STUDY ASSISTANCE ALLOCATION IN YALIMO REGENCY, PAPUA - Reni Koibur; Linder Faluk; Axelon S. Renyaan (JTH: Journal of Technology and Health, 2026)
The Yalimo Regency Student Association in Indonesia and the local government require a valid and organized student database to support the distribution of study assistance. The existing recipient selection process was still conducted manually, causing long processing time, inefficient data search, and potential inconsistency in decision making. This study developed a decision support system for selecting study assistance recipients in Yalimo Regency using the Analytic Hierarchy Process (AHP). The system development process followed the System Development Life Cycle (SDLC), while AHP was applied to prioritize student alternatives based on four criteria: Grade Point Average (GPA), number of siblings, parents' income, and organizational position. The data processed in the system include student identity, semester, level of study, university, faculty, district of origin, and active academic status. The application was implemented as a web-based system using PHP and MySQL on the XAMPP environment. The system provides login access, student data management, master data management, criteria and alternative input, pairwise comparison processing, and final ranking reports. Black-box testing showed that the main system functions ran according to the expected requirements. The resulting system helps the Yalimo Regency Student Association and the Yalimo Regency Government organize student data and support a more structured, transparent, and efficient study assistance allocation process.